STUDI LITERATUR SIKAP DOSEN DALAM MENDUKUNG KEBERHASILAN PENDIDIKAN TINGGI VOKASI (PTV) - Samsun Samsun; Netti Karnati (Jurnal Evaluasi dan Pembelajaran, 2023)
The aim of this research is to analyze lecturers' attitudes towards vocational education and their impact on the success of vocational education practice. Vocational education is a government program, where vocational education is education that supports improving skills, which is the government's focus on skills education, especially providing work-ready skills. The research uses a literature review study method with descriptive analysis techniques. used to collect data. There are 11 journals in the last 5 years that meet the criteria based on research results, character education has been taught from an early age, so that character education in higher education is at the strengthening stage. The method used in providing lecturer attitude training at Vocational Higher Education (PTV) is attitude education carried out by the entire academic community. Attitude education at PTV is more flexible because the curriculum at PTV adapts to the needs of stakeholders (hospitals or the health sector).